Biological drugs in the treatment of atopic dermatitis – current recommendations of the Polish Dermatological Society, the Polish Society of Allergology, the Polish Pediatric Society and the Polish Society of Family Medicine - Nowicki, Roman; Trzeciak, Magdalena; Rudnicka, Lidia; Szepietowski, Jacek; Kulus, Marek; Kupczyk, Maciej; Mastalerz-Migas, Agnieszka; Peregud-Pogorzelski, Jarosław; Jahnz-Różyk, Karina; Narbutt, Joanna; Czarnecka-Operacz, Magdalena; Czajkowski, Rafał; et al. (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2020)
Atopic dermatitis (AD) is secondary to genetic, immunological and microbiological disorders as well as epidermal barrier defects, which are the main targets of therapy. The disease proceeds with periodic exacerbations. Its development and course are influenced by numerous environmental and individual factors. In recent decades, in industrialized countries, there has been a threefold increase in the incidence of AD. There is also an increasing number of cases resistant to topical treatment. Effective treatment of AD should provide control of clinical symptoms, prevent exacerbations and improve the quality of life of patients. The multifactorial etiopathogenesis and various endotypes and phenotypes of AD justify the tendency to optimize and personalize the therapy. Currently, we recommend the use of dupilumab for the treatment of patients from 12 years of age with moderate and severe atopic dermatitis, who do not respond to topical treatment.